CHILDREN'S RIGHTS BEFORE THE LAW: A ROLE OF LOCAL GOVERNMENT IN THE CHILD PROTECTION SYSTEM - Hatija Asiri; Andi Sugirman (Al-Bayyinah, 2020)
Protection of children's rights before the law has been regulated in Law No. 11 of 2012 concerning the child protection system and is specifically followed up in the Local Regulation of Bone Regency No. 1 of 2014. Children's inability in legal matters makes the State provide protection to children in conflict with the law. Legal protection for children is the obligation of the State as a mandate of the 1945 Constitution. The problem that arises is that cases of children dealing with the law continue to increase, so it is important to see the form of the role of the government in giving rights to children in conflict with the law. This research is a normative empirical study with a normative juridical legal research approach. Analyzing legal theories and statutory regulations, comparison of laws (comparison approach). The findings of this study indicate that children who are in conflict with the law, the government has provided diversion protection, namely protection at the level of the judicial process, investigation and prosecution. The position of diversion is given by the government to children as victims, perpetrators and witnesses in criminal acts. Local governments in providing productive protection for children in trouble by providing educational and economic assistance. The implication of this finding shows that children are the generation of the nation who deserve protection from the State, even though these children are in conflict with the law.